The monsters we defy - Penelope, L., 1978- (Redhook, 2022)
"In the summer of 1925, along Washington, DC's "Black Broadway", a malevolent entity has begun preying on Negro residents. Twenty-three-year-old Clara Johnson is determined to discover what's going on in her community. Using her natural ability to talk with spirits, she begins to investigate, but a powerful spirit tasks her with a difficult quest: steal an ancient, magical ring from the finger of a wealthy socialite. When Clara meets Israel Lee, a supernaturally enhanced jazz musician also vying for the ring, the two decide to work together. They put together an unlikely team including a former circus freak, a pickpocketing Pullman Porter, and an aging vaudeville actor to pull off an impossible heist. But a dangerous spirit interferes at every turn and conflict in the spirit world is leaking out into the human world. With different agendas, even if Clara and Israel pull off the heist, only one of them can truly win"--